UTILIZAÇÃO DE PASTILHAS DE PELTIER PARA OTIMIZAÇÃO DO RESFRIAMENTO E DESEMPENHO DE PROCESSADORES - de Camargo Fantin, Vinicius; Wonzoski, Fabiano Oliveira (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2025)
Processor overheating is one of the main factors that compromise the performance and lifespan of computational systems. As an alternative, Peltier modules offer localized cooling through the thermoelectric effect, transferring heat quickly and efficiently. This research advances initial studies by integrating simulations with Arduino microcontrollers and practical tests, aiming for higher energy efficiency and thermal stability. The objective of the study is to implement and optimize the use of Peltier modules for processor cooling, exploring control strategies with sensors, Arduino programming, and virtual simulations in Tinkercad. The project seeks to reduce energy consumption, improve heat dissipation on the hot side of the module, and validate the effectiveness of control algorithms such as Proportional-Integral-Derivative (PID) to maintain stable operating temperatures. The methodology was developed in two stages. In the first stage, the architecture of the motherboard and the integration of the Peltier module with the processor were studied. Practical tests were conducted using discarded processors to evaluate thermal behavior and power consumption, with sensors, varied power supplies, and different Peltier models (TEC-12706 and TEC-12715). In the second stage, Tinkercad was employed to validate the control logic. The LM35 sensor, connected to Arduino, simulated thermal variations by triggering LEDs, resistors, and fans as substitutes for the actual Peltier device. Despite the platform’s limitation in simulating thermoelectric components directly, this approach enabled code refinement, simplified PID control testing, and the assessment of hysteresis and thermal response time. The results confirmed the effectiveness of Peltier-based cooling but highlighted the need for auxiliary dissipation systems, such as fans or water cooling, to manage the hot side of the module. PID control proved promising in minimizing abrupt temperature fluctuations and enhancing system stability. Furthermore, the Tinkercad simulations, though abstract, provided a reliable logical foundation for practical implementation, helping to optimize code and anticipate real-world scenarios. The study concludes that integrating Peltier modules into processor cooling systems is both viable and efficient, particularly when combined with automated thermal control strategies. However, challenges such as energy consumption and heat dissipation remain critical considerations. Future work may include the development of hybrid systems that combine Peltier devices with water cooling and advanced control algorithms, aiming for greater efficiency and reliability in high-performance computing environments.